2017
DOI: 10.1542/peds.2015-4626
|View full text |Cite|
|
Sign up to set email alerts
|

Project IMPACT Pilot Report: Feasibility of Implementing a Hospital-to-Home Transition Bundle

Abstract: A pediatric care transition bundle was successfully tested and implemented, as demonstrated by improvement in all process measures, as well as caregiver home management skills. Important considerations for successful implementation and evaluation of the discharge bundle include the role of local context, electronic health record integration, and subgroup analysis for technology-supported patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
(30 reference statements)
0
35
0
Order By: Relevance
“…** Both studies in which PCIs were evaluated (1 prepost study that was focused on children with multisystem complex illnesses and 1 prospective cohort study that was focused on the general population of children hospitalized) revealed an association with improved satisfaction. 43,86 CCIs were also associated with improved satisfaction across patient populations, including effective studies in children with chronic illnesses (n = 7), 43,44,48,49,52,53,64 patients in the NICU (n = 2), 78,80 and the general hospitalized population (n = 4). 86,87,89,94 CCIs that were associated with improved satisfaction included assistance with scheduling follow-up care, 43,53,89 in-home visits or follow-up telephone calls, 44,48,49,53,64,86,94 and intensive discharge planning.…”
Section: Results Of Individual Studies Regarding Patient And/or Caregmentioning
confidence: 99%
See 3 more Smart Citations
“…** Both studies in which PCIs were evaluated (1 prepost study that was focused on children with multisystem complex illnesses and 1 prospective cohort study that was focused on the general population of children hospitalized) revealed an association with improved satisfaction. 43,86 CCIs were also associated with improved satisfaction across patient populations, including effective studies in children with chronic illnesses (n = 7), 43,44,48,49,52,53,64 patients in the NICU (n = 2), 78,80 and the general hospitalized population (n = 4). 86,87,89,94 CCIs that were associated with improved satisfaction included assistance with scheduling follow-up care, 43,53,89 in-home visits or follow-up telephone calls, 44,48,49,53,64,86,94 and intensive discharge planning.…”
Section: Results Of Individual Studies Regarding Patient And/or Caregmentioning
confidence: 99%
“…43,86 CCIs were also associated with improved satisfaction across patient populations, including effective studies in children with chronic illnesses (n = 7), 43,44,48,49,52,53,64 patients in the NICU (n = 2), 78,80 and the general hospitalized population (n = 4). 86,87,89,94 CCIs that were associated with improved satisfaction included assistance with scheduling follow-up care, 43,53,89 in-home visits or follow-up telephone calls, 44,48,49,53,64,86,94 and intensive discharge planning. 43,48,53,64,78,80,87,94 Similarly, FEIs were associated with improved satisfaction in children with chronic illnesses (n = 9), † † neonates (n = 3), 72,75,78 and general pediatric patients in the hospital (n = 4).…”
Section: Results Of Individual Studies Regarding Patient And/or Caregmentioning
confidence: 99%
See 2 more Smart Citations
“…These barriers may have been heightened by the competing priorities faced by hospitalists including clinical duties, supervisory responsibilities, and administrative/non-clinical tasks. Potential strategies for improving adoption include more frequent eligibility screening, in-person discussion of recruitment at daily discharge planning rounds, discharge bundles to improve prediction of discharge timing [15], or opt-out formats with standardized scheduling of discharge videoconferences for all CMC.…”
Section: Discussionmentioning
confidence: 99%